2021
DOI: 10.3390/ijms22031035
|View full text |Cite
|
Sign up to set email alerts
|

Low Basicity as a Characteristic for Atypical Ligands of Serotonin Receptor 5-HT2

Abstract: Serotonin receptors are extensively examined by academic and industrial researchers, due to their vital roles, which they play in the organism and constituting therefore important drug targets. Up to very recently, it was assumed that the basic nitrogen in compound structure is a necessary component to make it active within this receptor system. Such nitrogen interacts in its protonated form with the aspartic acid from the third transmembrane helix (D3x32) forming a hydrogen bond tightly fitting the ligand in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(129 reference statements)
1
2
0
Order By: Relevance
“…In this context, the chemical transformation of a basic primary amine into an amide deserves comment. Recent studies have shown that low basicity ligands for serotonin receptors, including the serotonin1A receptor, do exist [56,57], and this validates the design of our NBD-labeled probes using the reactive amine group. This could accoun for some loss in affinity of these ligands for the serotonin1A receptor (see later).…”
Section: Design Of the Fluorescent Analogs Of Serotoninsupporting
confidence: 71%
“…In this context, the chemical transformation of a basic primary amine into an amide deserves comment. Recent studies have shown that low basicity ligands for serotonin receptors, including the serotonin1A receptor, do exist [56,57], and this validates the design of our NBD-labeled probes using the reactive amine group. This could accoun for some loss in affinity of these ligands for the serotonin1A receptor (see later).…”
Section: Design Of the Fluorescent Analogs Of Serotoninsupporting
confidence: 71%
“…In this review, we will focus our attention on TCC, a small molecule also named 3,4,4′-trichlorocarbanilide that belongs to the class of diarylures or bis-arylureas. This interesting class of compounds has been recently reviewed by our research group as anticancer agents [ 6 ], and then, due to their multiple actions [ 7 , 8 , 9 , 10 , 11 ], they were also suggested for repositioning to antimicrobial agents and/or potential treatment for new pandemics, as COVID-19 [ 12 , 13 ]. TCC is a common ingredient in personal care products, especially dermal cleaning products such as antibacterial bar/Liquid soaps, body lotions, deodorants, detergents, medical disinfectants, aftershave soaps, hand sanitizers, toothpaste, handwash and mouthwash, body washes, cleansing lotions, baby teethers and wipes for its sanitizing properties and detergents [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will focus our attention on TCC, a small molecule also named 3,4,4trichlorocarbanilide that belongs to the class of diarylures or bis-arylureas. This interesting class of compounds has been recently reviewed by our research group as anticancer agents [6], and then, due to their multiple actions [7][8][9][10][11], they were also suggested for Since its advent in 1957 [22], TCC has been produced and used on a large scale, and its consumption from personal care products in the United States reached 500,000-1,000,000 pounds per year [23]. The 2013-2014 National Health and Nutrition Examination Survey showed that 36.9% of the urine samples in the United States (U.S.) contained TCC [24].…”
Section: Introductionmentioning
confidence: 99%